The effects of BMS-470539 on lipopolysaccharide-induced acute lung injury - Jang, Eun-A (Acute Crit Care, 2019)
BACKGROUND: Overactivation of inflammatory cells, including macrophages and neutrophils, is associated with acute lung injury. BMS-470539 is a selective agonist of melanocortin 1 receptor, which triggers the inhibition of proinflammatory responses, suppressing neutrophil infiltration and protecting tissue. This study evaluated the effects of BMS-470539 on lipopolysaccharide-induced acute lung injury in a mouse model. METHODS: Mice received a subcutaneous injection of saline or BMS-470539 (18.47 mg/kg) 1 hour before an intratracheal injection of saline or lipopolysaccharide (20 μg). Mice were sacrificed to analyze the severity of pulmonary edema (lung wet-to-dry weight [W/D] ratio) and inflammatory responses (level of leukocytes, polymorphonuclear neutrophils [PMNs] and tumor necrosis factor alpha [TNF-α] in bronchoalveolar lavage fluid [BALF]), and neutrophil infiltration (myeloperoxidase activity). TNF-α activation was also measured in neutrophils from bone marrow. Survival was investigated in a second-hit sepsis mouse model. RESULTS: BMS-470539 improved sepsis-induced pulmonary edema, as demonstrated by a decreased W/D ratio (5.76%±0.83% to 3.81%±0.86%, P<0.05). The inflammatory response also improved, as shown by decreased levels of leukocytes (551±116 to 357±86×10²/mm³, P<0.05), PMNs (51.52%±16.23% to 18.41%±7.25%, P<0.01), and TNF-α (550±338 to 128±52 pg/ml, P<0.01) in the BALF. BMS-470539 also improved the inflammatory response, as shown by TNF-α levels (850±158 to 423±59 pg/ml, P<0.01) in neutrophils. BMS-470539 downregulated neutrophil infiltration in the lung (myeloperoxidase: 654±98 to 218±89 U/g, P<0.001). Lastly, BMS improved the survival rate (0% to 70%, P<0.01) in a mice multiple organ failure model. CONCLUSIONS: BMS-470539 improved lipopolysaccharide-induced acute lung injury and mortality in mice by affecting the inflammatory response.